Decision Support System for KIP Universitas Global Jakarta Scholarship Recipients Using the Simple Additive Weighting (SAW) Method - Harjiyanto, Kun; Ekawati, Risma; Anjara, Febria; Jaenul, Ariep (Jurnal Teknologi Informasi dan Pendidikan, 2024)
In accordance with the explanation of article 76 UU No.12 Tahun 2012 about Higher Education. In article 76 Paragraph 1 Explained that, "The Government, Local Government, and/or Universities are obliged to fulfill the rights of economically disadvantaged students to be able to complete their studies by academic regulations". As for those who were accepted, only 61,067 participants were. They are scattered in various colleges. Based on the technical guidelines for the implementation of the KIP Kuliah 2021 selection for the Education Financing Service Center of the Direktorat Jenderal Pendidikan Tinggi Kementerian Pendidikan dan Kebudayaan Republik Indonesia, several criteria must be met by prospective students. The results of the absolute requirements are then re-selected in the form of academic ability tests and interviews conducted to capture assistance so that they are right on target. Based on the number of prospective enthusiasts who register, the registration process takes a lot of time, starting from the selection process for completeness of documents, and academic potential tests, to interviews. In its implementation, choosing prospective students who are by the criteria requires more time and allocation of human resources, so this research is expected to make it easier for universities to monitor the activities of KIP Kuliah recipient students and make it easier to evaluate students on the results of the scores that have been obtained